Antacid exposure and immunotherapy outcomes among patients with advanced hepatocellular carcinoma. (April 2021) - Jun, Tomi; Ozbek, Umut; Dharmapuri, Sirish; Hardy-Abeloos, Camille; Zhu, Huili; Lin, Jung-Yi; Personeni, Nicola; Pressiani, Tiziana; Nishida, Naoshi; Lee, Pei-Chang; Lee, Chieh-Ju; Hildebrand, Hannah; et al.
Background: Antibiotic exposure has been associated with worse outcomes with immune checkpoint inhibitors (ICIs) in cancer patients, likely due to disruption of the gut microbiome. Other commonly prescribed medications, such as proton pump inhibitors (PPIs) and histamine-2-receptor antagonists (H2RAs), are also known to disrupt the microbiome, but data on their association with ICI outcomes are conflicting. Methods: We conducted a retrospective, multicenter, international cohort study including 314 hepatocellular carcinoma (HCC) patients treated with ICIs from 2017 to 2019 to assess the association between PPI or H2RA exposure (up to 30 days before ICI) and overall survival. Secondary outcomes included overall response rate (ORR) and development of any treatment-related adverse events (AEs). Results: Baseline PPI/H2RA exposure was not associated with overall survival in univariable (HR 1.01, 95% CI 0.75–1.35) or multivariable analysis (HR 0.98, 95% CI 0.71–1.36). Baseline PPI/H2RA exposure was not associated with either ORR (OR 1.32, 95% CI 0.66–2.65) or AEs (OR 1.07, 95% CI 0.54–2.12) in multivariable analysis. Conclusions: Our results suggest that exposure to PPI/H2RA prior to ICIs does not adversely affect outcomes in HCC patients.